Development and validation of critical reading intention scale (CRIS) for university students using exploratory and confirmatory factor analysis / Nadia Anuar, Ahmad Mazli Muhammad and Zainudin Awang - Anuar, Nadia; Muhammad, Ahmad Mazli; Awang, Zainudin (Universiti Teknologi MARA, 2023)
Critical reading is a crucial skill that students should acquire upon completion of higher education to obtain employment opportunities. However, their level of critical reading skills has been reported to be unsatisfactory. This study aims to address this issue by developing and validating an instrument that examines the factors that influence students’ intention to participate in critical reading. The theory of planned behaviour was employed to develop an instrument for the Critical Reading Intention Scale (CRIS) to gain a deeper insight on this issue. This cross-sectional study collected 120 responses for a pilot study which were subjected to exploratory factor analysis (EFA) using SPSS. Findings from the EFA suggested one item to be deleted. Subsequently, 220 responses were gathered from the actual data collection, and the data were subjected to confirmatory factor analysis (CFA) using AMOS. The results concluded that CRIS instrument fulfils the requirements in CFA and is valid for measuring students’ intention to participate in critical reading. CRIS is useful to identify the enablers and difficulties that influence students’ intention in critical reading and for relevant stakeholders to take necessary steps to remedy students’ unsatisfactory critical reading performance and create an environment that fosters critical reading skills.